A new nomogram for the prediction of bone metastasis in patients with prostate cancer. Issue 11 (November 2021) - Bai, Gang; Cai, Zhonglin; Zhai, Xiuxia; Xiong, Jian; Zhang, Fa; Li, Hongjun
Objective: This study aimed to establish a new prognostic nomogram for bone metastasis in patients with prostate cancer (PCa). Methods: This study retrospectively analyzed clinical data from 332 patients diagnosed with PCa from 2014 to 2019, and patients were randomly divided into a training set (n = 184) and a validation set (n = 148). Multivariate logistic regression analysis was used to establish a prediction model based on the training set, and a nomogram was constructed for visual presentation. The calibration, discrimination and clinical usefulness of the model were evaluated using the validation set. Results: Total prostate-specific antigen, clinical tumor stage, Gleason score, prostate volume, red cell distribution width and serum alkaline phosphatase were selected as predictors to develop a prediction model of bone metastasis. After evaluation, the model developed in our study exhibited good discrimination (area under the curve: 0.958; 95% confidence interval: 0.93–0.98), calibration (U = 0.01) and clinical usefulness. Conclusions: The new proposed model showed high accuracy for bone metastasis prediction in patients with PCa and good clinical usefulness.